Correlation between sleep quality and physical fitness among medical students of Udayana University - Tandiono, Erick K.; Sundari, Luh P. R.; Primayanti, I. Dewa A. I. D.; Adiatmika, I. Putu G. (International Journal of Research in Medical Sciences, 2021)
Background: The development of era has caused many declines in the quality of human health for all people, especially students. Sedentary behavior plays an important role in affecting sleep quality for a student. Sleep quality has a lot of correlations with various aspects, such as physical fitness. Good quality sleep will give an opportunity for the body to restore muscular strength, prolong the life of body cells, increase well-being, and leading to good physical fitness as well. Objective of the study was to find out the correlation between sleep quality and physical fitness among medical students of Udayana University. Methods: This research was an observational study with a cross-sectional method using the PSQI (Pittsburgh Sleep Quality Index) questionnaires and HST (Harvard Step Test) to 50 respondents. Results: Fisher’s Exact Test results showed no relationship (p>0.05) between sleep quality and physical fitness in medical students. This condition can be influenced by several other factors such as genetic factors, physical activity, nutritional status as seen from the percentage of fat, lifestyle, and psychological conditions. Conclusions: There is no correlation between sleep quality and physical fitness among medical student of Udayana University. Further research is needed related to other factors that affect medical student’s physical fitness.